A current model for FOI FinFETs with back-gate bias modulation. (November 2021) - Liu, F.Y.; Zhang, X.; Zhang, F.Y.; Li, B.; Li, B.H.; Huang, Y.; Wang, G.Q.; Chen, S.Y.; Zhang, Q.Z.; Yin, H.X.; Luo, J.J.; Han, Z.S.; et al.
Highlights: In this paper, the current model of FOI (Fin-On-Insulator) FinFETs is developed, in which the back-channel current is modeled as a parasitic transistor. This current model exhibits a wide valid range for various geometry parameters. It is demonstrated that the decreasing fin bottom angle may be useful to boost the drive capability of FOI FinFETs. Abstract: The current model of FOI (Fin-On-Insulator) FinFETs was developed, in which the back-channel current was modeled as a parasitic transistor. Both the experimental and TCAD simulation results validated the accuracy of the proposed model under different back-gate biases. This current model exhibits a wide valid range for various geometry parameters including fin width, fin height, sidewall inclination angle, fin bottom angle and channel doping density. It was demonstrated that the fin bottom angle had a great influence on the channel current when a positive back-gate bias applied, which may be useful to boost the drive capability of FOI FinFETs. Besides, the mobility influence on our model is also discussed. The proposed model can help to build BSIM model and instruct devices designer to optimize the performance of the devices.